Postcard from Nurse Margaret Ripley in Dunkirk to her mother, sent 21... - whatsthatpicture from... (Wikimedia Commons, 2011)
Notice image issue de Wikimedia Commons. Titre: Postcard from Nurse Margaret Ripley in Dunkirk to her mother, sent 21 March 1915 (6270428460). Sent by a nurse, Margaret Ripley, to her mother back in England. As far as I can tell (corrections and additions welcome) this reads: " Just had your letter of 19th. Hope you have got home safe without further excitements. Wrote you letter yesterday to E[astbourne] so hope it will reach you. We always go over this part when going into D[unkerque]. Love to Beryl I hope she will find her voice in Syd[enham]. Just had a walk & got your card of 17th they had kept it at 13 Depot. Went to church yesterday eve - long walk on sands in afternoon lovely sunshine. Heaps of aeroplanes & in night too or rather 10pm. Love to all. Hope Horace is quite well again. Mar " For more details of the story behind this album see www.flickr.com/photos/whatsthatpicture/sets/7215762769463...
Licence CC BY 2.0 via Wikimedia Commons
Keywords: carte postale; image; patrimoine; architecture; histoire locale; église; transport